2018
DOI: 10.3389/fmicb.2018.00108
|View full text |Cite
|
Sign up to set email alerts
|

Compatible Solute Synthesis and Import by the Moderate Halophile Spiribacter salinus: Physiology and Genomics

Abstract: Members of the genus Spiribacter are found worldwide and are abundant in ecosystems possessing intermediate salinities between seawater and saturated salt concentrations. Spiribacter salinus M19-40 is the type species of this genus and its first cultivated representative. In the habitats of S. salinus M19-40, high salinity is a key determinant for growth and we therefore focused on the cellular adjustment strategy to this persistent environmental challenge. We coupled these experimental studies to the in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 123 publications
(300 reference statements)
0
22
0
Order By: Relevance
“…Several studies have tried to analyze the mechanisms by which bacteria can improve the resistance in plants. Hence, some research shows that the use of PGP bacteria can promote plant growth and enhance salt tolerance capacity by inducing synthesis of osmolytes (Siddikee et al, 2011;Chanratana et al, 2017;Karnwal, 2017;León et al, 2018). Our results revealed that after evaluation, we selected Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies have tried to analyze the mechanisms by which bacteria can improve the resistance in plants. Hence, some research shows that the use of PGP bacteria can promote plant growth and enhance salt tolerance capacity by inducing synthesis of osmolytes (Siddikee et al, 2011;Chanratana et al, 2017;Karnwal, 2017;León et al, 2018). Our results revealed that after evaluation, we selected Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 84%
“…1, Table 1). The possible mechanism that allows this tolerance to salt, halotolerant bacteria are able under elevated salt concentration to use microbial adaptive responses to high-osmolarity stress by the accumulation of compatible solutes either synthesis or uptake (Aslam and Ali, 2018;León et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the GB content steeply increased under salt stress in another halophytic species, Suaeda aegyptiaca indicating towards the stress-induced metabolic plasticity existing across plant species [88]. Leon et al [89] also reported the effectiveness of GB and arsenobetaine in ameliorating salt-induced damages in the halophile, Spiribacter salinus. The radiolabeled GB was used to study its transport, and it was observed that the GB pool was intricately associated with the presence of salt in the growth medium.…”
Section: Saltmentioning
confidence: 99%
“…Many representatives with re-arranged or disentangled ect biosynthetic genes live in marine ecosystems [ 199 ]. Given the re-arrangement of the canonical ect gene configuration in these bacteria, one wonders if they are capable of ectoine/5-hydroxyectoine production.…”
Section: Genetics and Phylogenomics Of Ectoine And 5-hydroxyectoinmentioning
confidence: 99%